2018
DOI: 10.1007/s11606-018-4434-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Medical Scribes on Physician and Patient Satisfaction in Primary Care

Abstract: In an academic GIM setting, employment of a scribe was associated with improved physician satisfaction without compromising patient satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
142
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 70 publications
(145 citation statements)
references
References 27 publications
(31 reference statements)
3
142
0
Order By: Relevance
“…Expanded care teams have demonstrated value in reducing physician EHR time in primary care. 20 Assisting physicians with certain clinical tasks may also increase physician well-being. 6 This organization has taken recent steps to improve well-being, including creating an office of physician wellness, piloting multidisciplinary in-basket support, providing enhanced leadership development support and training, and implementing a primary care transformation program including in-basket support from APCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Expanded care teams have demonstrated value in reducing physician EHR time in primary care. 20 Assisting physicians with certain clinical tasks may also increase physician well-being. 6 This organization has taken recent steps to improve well-being, including creating an office of physician wellness, piloting multidisciplinary in-basket support, providing enhanced leadership development support and training, and implementing a primary care transformation program including in-basket support from APCs.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 Health systems are increasingly taking steps to enhance physician well-being. 19,20 For instance, the Mayo Clinic has used a bottom-up approach to tackling burnout using focus groups with physicians. 21 Other approaches target individual factors such as promoting resilience and mindfulness.…”
Section: Introductionmentioning
confidence: 99%
“…Several individual studies have described increased provider satisfaction, including one report from a family medicine clinic that showed that all measures of provider satisfaction significantly improved with utilization of scribes . Similarly, a study of six internal medicine physicians reported 100% satisfaction with clinic workflow in the primary care setting after implementation of a scribe program, compared to only 33% before the scribe program . Two studies in urology clinics also found that physicians were more satisfied with their workload and clinic hours when working with a scribe .…”
Section: Discussionmentioning
confidence: 99%
“…Although patients have reported positive attitudes toward scribes and perceived improvement of provider-patient interactions, [10][11][12] no studies have found a quantitative difference in patient's satisfaction with providers. 11,[13][14][15][16][17] Conclusions are further limited by heterogeneity in the methodology for assessing patient satisfaction in all of these studies, including many studies that created their own surveys and metrics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation